Validation of computerized square-drawing based evaluation of motor function in patients with stroke. (September 2019) - Isaković, Milica S.; Savić, Andrej M.; Konstantinović, Ljubica M.; Popović, Mirjana B.
Highlights: Novel low/high performance classification of stroke patients based on drawing test. Significantly different WMFT scores for low and high performance groups. High correlation between new drawing test kinematic metrics and WMFT score. Abstract: Human-administered clinical scales are commonly used for quantifying motor performance and determining the course of therapy in post-stroke individuals. Computerized methods aim to improve consistency, resolution and duration of patients' evaluation. The objective of this study was to test the validity of computerized square-drawing test (DT) for assessment of shoulder and elbow function by using novel set of DT-based kinematic measures and explore their relation with Wolf Motor Function Test (WMFT) scoring. Forty-seven stroke survivors were tested before and after the rehabilitation program. DT involved drawing a square in horizontal plane using a mechanical manipulandum and a digitizing board. Depending on the initial classification of patients into low or high performance groups, the two different outcome metrics were derived from DT kinematic data for evaluation of each group. Linear regression models applied to map DT outcome values to WMFT scores for both groups resulted with high correlation coefficients and low mean absolute prediction error. In conclusion, we have identified a set of kinematic measures suitable for fast and objective motor function evaluation and functional classification, strongly correlating with WMFT score in post-stroke individuals. The results support validation of square-drawing motor function assessment, encouraging its use in clinical settings.